2021
DOI: 10.1186/s12967-021-02813-6
|View full text |Cite
|
Sign up to set email alerts
|

Dodging COVID-19 infection: low expression and localization of ACE2 and TMPRSS2 in multiple donor-derived lines of human umbilical cord-derived mesenchymal stem cells

Abstract: Background Mesenchymal stem cells derived from human umbilical cord (hUC-MSCs) have immunomodulatory properties that are of interest to treat novel coronavirus disease 2019 (COVID-19). Leng et al. recently reported that hUC-MSCs derived from one donor negatively expressed Angiotensin-Converting Enzyme 2 (ACE2), a key protein for viral infection along with Transmembrane Serine Protease 2 (TMPRSS2). The purpose of this study was to quantify the expression of ACE2 and TMPRSS2 in hUC-MSCs lots deri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Avanzini et al ( 35 ) and Schäfer et al ( 36 ) in their in vitro studies found that both fetal and adult MSCs have a deficient expression of ACE2 and TMPRSS2. Hernandez et al ( 37 ) reported the same result in human UC-MSCs. However, Desterke et al ( 38 ) reported that adult MSCs express ACE2 highly, while placenta-derived MSCs express ACE2 at a low level and only in initial passages of cultures.…”
Section: Discussionmentioning
confidence: 54%
“…Avanzini et al ( 35 ) and Schäfer et al ( 36 ) in their in vitro studies found that both fetal and adult MSCs have a deficient expression of ACE2 and TMPRSS2. Hernandez et al ( 37 ) reported the same result in human UC-MSCs. However, Desterke et al ( 38 ) reported that adult MSCs express ACE2 highly, while placenta-derived MSCs express ACE2 at a low level and only in initial passages of cultures.…”
Section: Discussionmentioning
confidence: 54%
“…Another study demonstrated that AT-MSCs have more potent immunomodulatory properties and exhibit greater IDO production compared to BM-MSCs ( 73 ). For the treatment of COVID-19 it may be important to select tissue sources that yield MSCs with reduced expression or lack of the ACE2 receptor ( 74 , 75 ). This could allow MSCs to persist longer following administration in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, reported data is variable. In such a study, MSCs were reported to lack ACE2 and TMPRRS2 expressions [69][70][71], while other studies showed that ACE2 was highly expressed in MSCs derived from adult bone marrow, adipose tissue or umbilical cord [72,73]. Some studies also showed that ACE2 expression provides protective roles to MSCs against SARS-CoV-2 infection [74,75].…”
Section: Mesenchymal Stem Cell Therapymentioning
confidence: 99%